(untitled) (Research, Society and Development, 2025)
Obesity is a multifactorial condition and one of the greatest global public health challenges, with an etiology that goes beyond simple energy balance. Long-term weight maintenance is hindered by a complex interaction of physiological and behavioral mechanisms. This article aimed to investigate the main mechanisms that hinder sustained weight loss and its maintenance, including metabolic adaptation, changes in the homeostatic appetite system, and behavioral aspects. This is a literature review conducted in databases such as PubMed, SciELO, CAPES Journals Portal, and MPDI. The analysis revealed that metabolic adaptation, characterized by a disproportionate drop in energy expenditure, persists even after weight loss, although its clinical relevance under energy balance neutrality remains debated. Moreover, weight reduction triggers lasting hormonal changes, such as increased ghrelin and decreased leptin and PYY levels, which heighten hunger and reduce satiety, contributing to weight regain. Behavioral and environmental factors—such as stress, poor sleep, and an obesogenic environment—amplify these effects. It is concluded that the maintenance of weight loss is challenged by the interaction of these biological and behavioral factors. A deep understanding of these mechanisms is essential to develop more effective and sustainable nutritional strategies in clinical practice.